Big peptide drugs in a small molecule world - Otvos, Laszlo; Wade, John D. (Frontiers in Chemistry, 2023)
A quarter of a century ago, designer peptide drugs finally broke through the glass ceiling.Despite the resistance by big pharma, biotechnology companies managed to develop injectable peptide-based drugs, first against orphan or other small volume diseases, and later for conditions affecting large patient populations such as type 2 diabetes. Even their lack of gastrointestinal absorption could be utilized to enable successful oral dosing against chronic constipation. The preference of peptide therapeutics over small molecule competitors against identical medical conditions can be achieved by careful target selection, intrachain and terminal amino acid modifications, appropriate conjugation to stability enhancers and chemical space expansion, innovative delivery and administration techniques and patient-focused marketing strategies.Unfortunately, however, pharmacoeconomical considerations, including the strength of big pharma to develop competing small molecule drugs, have somewhat limited the success of otherwise smart peptide-based therapeutics. Yet, with increasing improvement in peptide drug modification and formulation, these are continuing to gain significant, and growing, acceptance as desirable alternatives to small molecule compounds.